The First Report of Polymorphisms and Genetic Characteristics of the Shadow of Prion Protein (SPRN) in Prion Disease-Resistant Animal, Chickens - Kim, Yong-Chan; Kim, Hyeon-Ho; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Prion diseases are irreversible and acute neurodegenerative disorders caused by the aggregated form of prion protein (PrPSc) derived from the normal form of prion protein (PrPC). Previous studies have reported that shadow of prion protein (Sho) interacts with prion protein (PrP) and accelerates the conversion of PrPC to PrPSc. In addition, genetic polymorphisms of the shadow of the prion protein gene (SPRN) are related to the vulnerability of prion diseases in various hosts. However, to date, polymorphisms and genetic features of the SPRN gene have not been investigated in chickens, which are prion disease-resistant animals. We investigated genetic polymorphisms of the SPRN gene in 2 breeds of chickens, i.e. Dekalb White and Ross, using Amicon sequencing. We analyzed genotype, allele and haplotype frequencies and linkage disequilibrium (LD) among the genetic polymorphisms. In addition, we compared the amino acid sequences of Sho among several prion-related species to identify the unique genetic features of chicken Sho using ClustalW. Furthermore, we evaluated the N-terminal signal peptide and glycosylphosphatidylinositol (GPI)-anchor using SignalP and PredGPI, respectively. Finally, we compared the number of SPRN polymorphisms between prion disease-resistant and prion disease-susceptible animals. We identified 7 novel single-nucleotide polymorphisms (SNPs), including 1 synonymous SNP in the open reading frame (ORF) of the chicken SPRN gene. We also found significantly different genotypes, allele frequencies and haplotypes between the 2 chicken breeds. In addition, we found that the interaction regions between Sho and PrP and the NXT glycosylation motif were conserved among all species. Notably, sequence similarity was extremely low in the N-terminal and C-terminal regions between mammals and chickens. Furthermore, we found that chicken Sho was the longest N-terminal signal peptide, and the amino acids of the cutting site of chicken are different from those of mammals. Last, unlike other species investigated, omega-site and signal sequences of the GPI-anchor were not found only in chickens. To the best of our knowledge, this is the first report of genetic polymorphisms of the SPRN gene in chickens.